The tectonics and three-dimensional structure of spreading centers--microearthquake studies and tomographic inversions - Toomey, Douglas R (Massachusetts Institute of Technology, 1987)
Thesis (Ph. D.)--Joint Program in Oceanography (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 1987. Supervised by Mike Purdy, Sean C. Solomon. Includes bibliographical references. Two-thirds of the Earth's surface has been formed along a global system of spreading centers that are presently manifested in several different structural forms, including the classic rift valley of the Mid-Atlantic Ridge, the more morphologically subdued East Pacific Rise, and the pronounced en echelon structure of the Reykjanes Peninsula within southwestern Iceland. In this thesis, each of these different spreading centers is investigated with microearthquake studies or tomographic inversion of travel times. Results of these studies are used to constrain the spatial variability of physical properties and processes beneath the axis of spreading and, together with other observations, the temporal characteristics of crustal accretion and rifting. In Chapter 2 the theoretical basis of seismic body-wave travel-time tomography and techniques for the simultaneous inversion for hypocentral parameters and velocity structure are reviewed. A functional analysis approach assures that the theoretical results are independent of model parameterization. An important aspect of this review is the demonstration that travel time anomalies due to path and source effects are nearly independent. The discussion of the simultaneous inverse technique examines theoretically the dependence of tomographic images on the parameterization of the velocity model. In particular, the effects of parameterization on model resolution are examined, and it is shown that an optimum set of parameters averages velocity over localized volumes. Chapter 2 ends with the presentation of the results of tomographic inversions of synthetic data generated for a model of the axial magma chamber postulated to exist beneath the East Pacific Rise. These inversions demonstrate the power of the ...